1999
DOI: 10.1136/jnnp.66.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of 99mTc-ECD and 99mTc-HMPAO for peri-ictal SPECT: qualitative and quantitative analysis

Abstract: Tc-HMPAO, thereby enhancing the sensitivity and the specificity of peri-ictal SPECT for the localisation of intractable partial epilepsy. (J Neurol Neurosurg Psychiatry 1999;66:331-339) Keywords: Ictal SPECT;99m Tc-ECD; 99m Tc-HMPAO Peri-ictal SPECT shows great promise as a tool to accurately localise seizures in intractable partial epilepsy, particularly in those with temporal lobe seizures. [1][2][3][4][5][6] Moreover, the recent development of computer aided methods of subtracting the interictal SPECT im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 32 publications
1
33
4
Order By: Relevance
“…99m Tc-HMPAO must be constituted immediately before injection, and this delay results in more postictal injections than would occur with use of 99m Tc-ECD. 17 The conventional method of visually comparing ictal with interictal SPECT images has been reported to yield an abnormal focus in as many as 90% of patients with TLE, 18 whereas the rate of STATISCOM detection (84%) and SISCOM detection (66%) of an abnormal focus in our study are lower. However, many conventional visual comparison studies were not blinded to the results of all other diagnostic information, and the reference for localization was scalp EEG findings.…”
Section: Discussioncontrasting
confidence: 47%
“…99m Tc-HMPAO must be constituted immediately before injection, and this delay results in more postictal injections than would occur with use of 99m Tc-ECD. 17 The conventional method of visually comparing ictal with interictal SPECT images has been reported to yield an abnormal focus in as many as 90% of patients with TLE, 18 whereas the rate of STATISCOM detection (84%) and SISCOM detection (66%) of an abnormal focus in our study are lower. However, many conventional visual comparison studies were not blinded to the results of all other diagnostic information, and the reference for localization was scalp EEG findings.…”
Section: Discussioncontrasting
confidence: 47%
“…T-contrasts were defined, and results displayed with a significance threshold of P < 0.001 (not corrected for multiple comparisons), and a cluster-level threshold of 125 contiguous voxels (1 cm 3 ) was used (McNally et al, 2005). Prior studies have shown some differences in the uptake patterns of Tc-99m ECD, Tc-99m HMPAO, and other tracers (O'Brien et al, 1999;Inoue et al, 2003). To assess differences in observed asymmetry between different SPECT tracers, we obtained 14 sets of paired resting HMPAO SPECT images of normal volunteers from the Yale University Epilepsy Research Group (http://spect.yale.…”
Section: Statistical Parametric Mappingmentioning
confidence: 99%
“…99m Tc-Bicisate was the preferred brain imaging agent at our institution because the early formulation of 99m Tc-exametazime limits stability after reconstitution. Additionally, activity was higher if the agent could be reconstituted with a cold kit (3). The use of 99m Tc-exametazime to evaluate patients with epilepsy has lower localization rates, poorer interobserver agreement, and less concordance with electroencephalogram findings, MRI findings, and discharge diagnosis than does the use of 99m Tc-bicisate.…”
Section: Discussionmentioning
confidence: 99%
“…This study was presented at the Society of Nuclear Medicine Annual Meeting, San Diego, California, June [3][4][5][6][7] 2006.…”
Section: Acknowledgmentsmentioning
confidence: 99%